Making Remittances Work: Balancing Financial Integrity and Inclusion - Todoroki, Emiko (World Bank, 2015)
H.M. Queen Máxima of the Netherlands, United Nations Secretary-General?s Special Advocate for Inclusive Finance for Development stated that ?the impact of helping migrants and their families will be lasting and global if we link remittances to other financial services and make them more affordable and more relevant to their needs.?